Consumen Laptop Service Notification System In Android-Based Family Computer Shops - Iskandar; Alvin, Muhammad; Hayadi, B. Herawan; Lubis, Adyanata (Journal of ICT Applications System, 2022)
Currently the Family Computer store already has 3 branches and for sales matters it implements an offline and online system. But at this time the store still uses an offline system in terms of service matters such as: Warranty Claims, Service, and Current Status Checks.For this reason, research was carried out which aims to create a program to provide services online so that users when there are problems can provide easier access.This research was made after passing observations and interviews from local parties. Making this program uses the Android Studio application to create an Android application where almost everyone has an Android cellphone, and uses the Firebase Cloud Messagging feature from Google to provide service access to users so that users can monitor and get the latest information from the program without having to come to the store. or notify the admin at the store